2022
DOI: 10.3389/fphar.2022.820971
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine as a Treatment for Osteoarthritis: What If It’s True?

Abstract: No disease-modifying treatments are currently available for osteoarthritis (OA). While many therapeutic approaches are now being investigated it is ethical to resort to alternative solutions as that we already possess. There are many reasons for thinking that, at sufficiently high doses, glucosamine (GlcN) sulphate possesses a clinically relevant effect on OA pain. Wide inter-individual variations in the symptomatic effects of GlcN are explained by the extreme variability of its bioavailability. In studies eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…2-amino-2-deoxy-β-d-glucopyranose (glucosamine) is widely used to improve the symptoms and to delay the structural progression of OA ( Conrozier & Lohse, 2022 ). Glucosamine is an effective autophagy activator, and autophagy enhancement mainly depends on the Akt/FOXO/mTOR pathway ( Caramés et al, 2013 ).…”
Section: Drugs Targeting Autophagy For Osteoarthritis Treatmentmentioning
confidence: 99%
“…2-amino-2-deoxy-β-d-glucopyranose (glucosamine) is widely used to improve the symptoms and to delay the structural progression of OA ( Conrozier & Lohse, 2022 ). Glucosamine is an effective autophagy activator, and autophagy enhancement mainly depends on the Akt/FOXO/mTOR pathway ( Caramés et al, 2013 ).…”
Section: Drugs Targeting Autophagy For Osteoarthritis Treatmentmentioning
confidence: 99%
“…In the United Kingdom (UK) 20% to 30% of elders over 60 years have symptomatic osteoarthritis. In the Middle East, more than one million people suffer from OA in Iraq, Yemen, Saudi Arabia, and Syria (7) In Egypt prevalence of OA is 8.5% in the total adult population, approximately 85% of individuals over the age of 75 years of age experience some symptoms of osteoarthritis. 40% of individuals with the disorder experience significant difficulties with daily activities to the point of interfering with workrelated or social roles.…”
Section: Introductionmentioning
confidence: 99%
“…Along with these therapies, the use of Glucosamine (GlcN) and its derivatives has become widespread in the last few decades, especially as food supplements added to a composition of nutraceuticals [ 13 ]. Clinical trials confirmed that glucosamine sulphate, at high doses, is the most active molecule to treat OA pain [ 14 , 15 ]. On the other hand, any current reformulation of GlcN was poorly able to increase drug delivery or efficacy [ 16 ].…”
Section: Introductionmentioning
confidence: 99%